"Aliens Ministering to Aliens": Reformed Church in America Missionaries among Chinese in the Philippines. (July 2018) - White, Chris
This article reviews the two decades after RCA missionaries were forced out of China, revealing that the church's "China mission" was not abandoned, but simply changed geographic focus to overseas Chinese in the Philippines. Although the RCA continued a ministry targeting Chinese from South Fujian, where they had worked since 1842, they faced many new challenges in the Philippines that were quite inconsistent with their experience in China. A major point of contention for missionaries was balancing their relationship with the United Church of Christ in the Philippines (UCCP) and Chinese churches that refused to join this ecumenical organization.